THE NATION'S ABILITY TO RESPOND TO THE CHALLENGES OF GLOBALIZATION IN THE CONTEXT OF EDUCATION - Siti Nurmela; Yulianti; Hobir Asyari; Hafidin Nurhadi; Uus Ruswandi (Universitas PGRI Palembang, 2023)
This research aims to find out the background of the concept of globalization, the positive and negative impacts of globalization, as well as the efforts and abilities of the Indonesian nation in responding to the challenges of globalization, especially in the field of education. This research uses a library research method or often called library research, with the aim of providing comprehensive research results from various points of view so that it becomes an interdisciplinary and multidisciplinary study. The results showed that globalization and its various challenges have become something that cannot be avoided. So that the nation's ability to answer its challenges still needs to be pursued and fought together. Globalization with its various forms, is no longer for us to question, but for us to take advantage of it well, and we fortify its negative impact through global education that cannot be separated from character education. So that the nation's children are able to take advantage of the positive impacts of globalization wisely and at least avoid its negative impacts.